The Fluidity of Otherness in John Yau’s Selected Poems - Alkass , Asst. Prof. Anan J. Lewis Yousif,PhD (Thi Qar Arts Journal, 2021)
Ever since the 1970s Asian American literature emerged to tackle issues of Western racism against Asians, the importance of preserving the Asian ethnic heritage, and chiefly constructing a definite sense of identity based on self-definition. Celebrating the ethnic self and its nationality and language of origin as well as its traditional values from root culture are the most essential aspects that formed Asian American literature. Asian American writers came to be known for being a vital voice of justice for the marginalized members of their community who strive to preserve their culture in the face of ethnic segregation. However, John Yau (1950- ), a prominent contemporary Chinese American poet, goes beyond self-identified poetic writings of the ethnic self, challenging the cultural stereotypical molds of the American mainstream that encapsulated the Asian American identity. Instead of promoting the preservation one’s ethnic and cultural indentity, Yau evokes an unsettling image of fluid ‘Otherness’ that does not yield to prescribed representations. The purpose of this paper is to examine Yau’s poetic vision of otherness and its significance by exploring a selection of his poems, mainly “Ing Grish,” arguing for an anti-essentialist notion of constructing the Asian American identity that is not based on one’s culture of origin. Tackling the poet’s unorthodox presentation of the ethnic self of Chinese Americans, the paper also emphasizes that within the fluid culture of contemporary America, the Asian American identity is necessarily unsettling, but liberated from rigid predicate identities and cultural classifications